2022
DOI: 10.1039/d1tc04697g
|View full text |Cite
|
Sign up to set email alerts
|

Paper-based flexible strain and pressure sensor with enhanced mechanical strength and super-hydrophobicity that can work under water

Abstract: Paper-based flexible sensors have attracted much attentions due to their abundant resource, low cost and good degradability in natural environment that are free of electronic waste (e-waste). However, the mechanical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 76 publications
4
17
0
Order By: Relevance
“…In comparison to previously reported paper-based flexible sensors, we found that the sensor developed in this work was the only one that demonstrated the ability to detect strain and pressure under water, as shown in Figure . ,,,, Furthermore, the sensor here exhibits long-term working stability over 10,000 cycles for both strain and pressure detection. As far as we know, this is the first instance of a paper-based sensor with multifunctionality and proven reliability under water (Table S1).…”
Section: Results and Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…In comparison to previously reported paper-based flexible sensors, we found that the sensor developed in this work was the only one that demonstrated the ability to detect strain and pressure under water, as shown in Figure . ,,,, Furthermore, the sensor here exhibits long-term working stability over 10,000 cycles for both strain and pressure detection. As far as we know, this is the first instance of a paper-based sensor with multifunctionality and proven reliability under water (Table S1).…”
Section: Results and Discussionmentioning
confidence: 56%
“…Comparison of multifunction, sustainability, strain durability and pressure durability under water, and WCA of paper-based superhydrophobic sensors. (AKD-coated paper, SiO 2 -coated paper, Hf-SiO 2 -coated paper, and PI tape-encapsulated paper …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our sensor, all materials including paper and ink are obtained from natural plants or/and animals. Paper and ink have huge advantages in recyclability, degradability, biocompatibility, and nontoxicity. Therefore, our all-paper sensors can be degraded by burial, incineration, solution treatment, and so on. , Figure a shows the process of degradation and recycling of our paper-based sensor. The sensor can be degraded into carbon dioxide, water, and potassium carbonate by incineration.…”
Section: Resultsmentioning
confidence: 99%